(untitled) (Minang Chemistry Journal (MCJ), 2026)
Zeolite nanocomposites were successfully synthesized from coal fly ash via hydro-thermal treatment. The structural and surface properties were evaluated using FTIR and SEM. Adsorption kinetics and isotherms of Pb(II) and Cd(II) ions from wastewater were investigated. The maximum adsorption capacity reached 85.5 mg/g for Pb(II), demonstrating that fly ash-derived zeolites are cost-effective adsorbents for toxic metal removal.